IMPACT OF FOLK DANCE ON PHYSICAL CONDITIONING OF YOUNGER SCHOOL-AGE CHILDREN - Ciematnieks, Uģis; Gulbe, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Children develop a variety of skills and knowledge from childhood, including physical activity habits that persist throughout their lives. Insufficient physical activity rates around the world are high and continue to increase (Latvian ministry of health, 2017). Dancing is one of the kinds of physical activity that can deliver benefits to health throughout life, even at the amateur level. Yet, it isn't quite clear yet whether dance intervention is as effective to health as other physical activities. (Yan, Cobley & Chan, 2018). The research question is – is it possible to increase general conditioning with folk dance classes besides a school activities? The aim of the study: explore the impact of folk dances on the children's body mass index and physical conditioning at a younger school age, compared with children engaged in other out of school physical activities and children not engaged in out of school physical activities. The study involved 117 children in age 9 -11 divided into three groups - going for folk dances after school, some kind of sport after school and without regular physical activity after school. The assessment of children's physical conditioning by the Eurofit tests showed a tendency that in average children's physical conditioning rates were “low“ or “below average” no matter in which group they are. For children who do afterschool activity as folk dance, BMI is statistically equivalent to those children who are going for other physical activities and children who are not engaged in any afterschool physical activity. The physical conditioning rates for all three groups are statistically equivalent in the tests: standing broad jump, bent arm hang, shuttle run 5x10m, while the test sit-ups the children lack of afterschool physical activity, average the result was one level lower than in the other groups. The main conclusion is, that volume of folk dance as afterschool physical activities is not enough to make significant difference of average physical conditioning level of children.